Islamic Business Ethics: Construction of Balance and Humanity Values - fiyatul Laily (IJED: International Journal of Economy Development Research, 2022)
Islamic economics provides guidance to humans in order to apply ethics in all aspects of life, including economic or business activities. Ethics is very important important to organize and provide direction to business people on matters good or bad, allowed or prohibited and right or wrong in carrying out activities the business. Business ethics in Islamic economics is contained in all aspects, both production, consumption and distribution. If business ethics is applied to all business activities, then it will directly create balance and prosperity together(maslahah) which leads to the achievement of essential welfare both in the world and in the world hereafter (falah).